المتكلم لدى طه عبد الرحمان وعبد الرحمان الحاج صالح من خلال كتابيهما اللسان والميزان أو التكوثر العقلي، الخطاب والتخاطب في نظرية الوضع والاستعمال دراسة تداولية مُقارِنة - خديجة حاج سعد, وهيبة هبيته (Univesity of El-Oued, 2022)
The pragmatic linguistic writings, in their various directions and concepts, start from a special view of the linguistic heritage. It is generally based on the issue of being influenced by Western (foreign) linguistic methods, such as structural, generative, phonetic, and others. In order to bring back those issues in a new dress that responds to the spirit of the modern era, and to shed light on the issues of the speaker and linguistic use. This research came to serve this procedural objective; By addressing the presentation and analysis of the efforts of two of these Arab pragmatic linguists, with whom no one differs in their excellence in the field of pragmatics, they are the scholar the father of linguistics "Abdul-Rahman Al-Hajj Saleh" and the pioneer of the deliberative trend "Taha Abdul-Rahman". And their view of the issues of the speaker, which we are going to study in this treatise, which is tagged with: “The Mutakallim of Taha Abd al-Rahman and Abd al-Rahman al-Haj Salih through their books, The Tongue and the Balance, or Mental Regeneration, and Discourse and Conversation in the Theory of Status and Use, a Comparative Pragmatic Study.” تنطلق الكتابات اللسانية التداولية بمختلف اتجاهاتها ومفاهيمها من نظرة خاصة إلى التراث اللغوي، تستند في عمومها على قضية التأثر بالمناهج اللسانية الغربية كالبنيوية والتوليدية والتلفظيّة وغيرها، وذلك لإعادة تلك القضايا بثوب جديد تستجيب لروح العصر الحديث، وتسليط الضوء على قضايا المتكلم واستعمال اللغة أثناء التخاطب. وقد جاء هذا البحث خدمة لهذا الهدف الاجرائي؛ من خلال التطرق بالعرض والتحليل لجهود اثنين من هؤلاء اللسانيين التداوليين العرب، الذين لا يختلف اثنين في تميّزهما في حقل البراغماتيك أو التداولية ، وهما العلامة أبو اللسانيات "عبد الرحمان الحاج صالح" ورائد الاتجاه التداولي "طه عبد الرحمان" ونظرتهما لقضايا المتكلم الذي نحن بصدد دراسته في هذه الرسالة الموسومة بـ: "المتكلم لدى طه عبد الرحمان وعبد الرحمان الحاج صالح من خلال كتابيهما اللسان والميزان أو التكوثر العقلي، والخطاب والتخاطب في نظرية الوضع والاستعمال دراسة تداولية مقارِنة"
Keywords: The speaker - foreign linguistics - pragmatics - Hajj Saleh - Taha Abd al-Rahman - discourse and communication - mental expansion: المتكلم – اللسانيات الغربية – التداولية – الحاج صالح - طه عبد الرحمان – الخطاب والتخاطب - التكوثر العقلي .